A randomized controlled trial comparing EMDR and CBT for obsessive–compulsive disorder. (28th July 2017) - Marsden, Zoe; Lovell, Karina; Blore, David; Ali, Shehzad; Delgadillo, Jaime
Abstract : Background: This study aimed to evaluate eye movement desensitization and reprocessing (EMDR) as a treatment for obsessive–compulsive disorder (OCD), by comparison to cognitive behavioural therapy (CBT) based on exposure and response prevention. Method: This was a pragmatic, feasibility randomized controlled trial in which 55 participants with OCD were randomized to EMDR ( n  = 29) or CBT ( n  = 26). The Yale‐Brown obsessive–compulsive scale was completed at baseline, after treatment and at 6 months follow‐up. Treatment completion and response rates were compared using chi‐square tests. Effect size was examined using Cohen's d and multilevel modelling. Results: Overall, 61.8% completed treatment and 30.2% attained reliable and clinically significant improvement in OCD symptoms, with no significant differences between groups ( p  > .05). There were no significant differences between groups in Yale‐Brown obsessive–compulsive scale severity post‐treatment ( d  = −0.24, p  = .38) or at 6 months follow‐up ( d  = −0.03, p  = .90). Conclusions: EMDR and CBT had comparable completion rates and clinical outcomes.